"All the problems in the community are multifaceted and related to each other": Inuit concerns in an era of climate change. Issue 4 (11th October 2020) - Ready, Elspeth; Collings, Peter
Abstract: Objective: Human dimensions of climate change research in the Arctic often proposes ways for local communities to adapt to changes to their environment, foregrounding problems posed by climate change while treating social, political, and economic factors as background conditions. We explore the relevance of this research paradigm for Inuit by examining how Inuit from Kangiqsujuaq present and discuss the major issues facing their community. Methods: We thematically code and analyze the responses of 107 Inuit to three free‐response questions about the problems facing their community and the best things about their community. The data were collected as part of a questionnaire for a project focused on food security and food sharing conducted in Kangiqsujuaq, Nunavik, in 2013 to 2014. Results: Few respondents mentioned issues relating to climate change among the most pressing problems faced by their community. Rather, a suite of interconnected social and economic issues, particularly substance abuse and the cost of living, emerged as the main concerns of Kangiqsujuarmiut. However, the environment was a central theme in respondents' favorite thing about their community. Conclusions: In light of the concerns identified by Inuit, we argue that much research on climate change makes incorrect a priori assumptions and consequently fails to capture aspects of Arctic socioecological systems that are essential for how Inuit are responding to climate change. An inductive, open‐ended approach can help produce research more relevant to communities.